Intelligent control of switch mode power supply (SMPS) for marine instrumentations [electronic resource] - Lee, Yee Hui, 1988-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Komputer)) - Universiti Teknologi Malaysia, 2011